Geography of a Displacement. The periurban circuit in Los siete locos by Roberto Arlt (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Madness in Los siete locos is the result of an attempt of integration into reality that is experienced by revolutionary characters, to whom that other type of sense is added; one which is openly opposed to the imperial logo that expels individuals who do not let themselves to be disciplined. Thus, in these characters there is an intensification of the insurrection and distinction from those who are disciplined. This allows the exploration of other places/non-places and also helps to map ―future settings‖ appropriate for the emergence of the new society. Arlt‘s madmen are not the result of a social mismatch but of an adaptation to the alienated conditions of the Buenos Aires society that they are part of.
Keywords: Madman; City; Deterritorialization; ―Other spaces‖; Heterotopy; Knowledge; Power